Assessment of cardiac patches suitability for tissue engineering - Madeddu, D.; Falco, A.; Frati, C.; Graiani, G.; Gervasi, A.; Lorusso, B.; Rosellini, E.; Rai, Ranjana; Boccaccini, Aldo R.; Lagrasta, C.; Quaini, F. (Vascular Pharmacology, 2015)

Bioactive Electrospun Fibers of Poly(glycerol sebacate) and Poly(ε-caprolactone) for Cardiac Patch Application - Rai, Ranjana; Tallawi, Marwa; Frati, Caterina; Falco, Angela; Gervasi, Andrea; Quaini, Federico; Roether, Judith; Hochburger, Tobias; Schubert, Dirk W.; Seik, Lothar; Barbani, Niccoletta; Lazzeri, Luigi; et al. (Advanced Healthcare Materials, 2015)
Scaffolds for cardiac patch application must meet stringent requirements such as biocompatibility, biodegradability, and facilitate vascularization in the engineered tissue. Here, a bioactive, biocompatible, and biodegradable electrospun scaffold of poly(glycerol sebacate)–poly(ε-caprolactone) (PGS–PCL) is proposed as a potential scaffold for cardiac patch application. The fibers are smooth bead free with average diameter = 0.8 ± 0.3 μm, mean pore size = 2.2 ± 1.2 μm, porosity = 62 ± 4%, and permeability higher than that of control biological tissue. For the first time, bioactive PGS–PCL fibers functionalized with vascular endothelial growth factor (VEGF) are developed, the approach used being chemical modification of the PGS–PCL fibers followed by subsequent binding of VEGF via amide bonding. The approach results in uniform immobilization of VEGF on the fibers; the concentrations are 1.0 μg cm−2 for the PGS–PCL (H) and 0.60 μg cm−2 for the PGS–PCL (L) samples. The bioactive scaffold supports the attachment and growth of seeded myogenic and vasculogenic cell lines. In fact, rat aortic endothelial cells also display angiogenic features indicating potential for the formation of vascular tree in the scaffold. These results therefore demonstrate the prospects of VEGF-functionalized PGS–PCL fibrous scaffold as promising matrix for cardiac patch application.

Biodegradable poly(glycerol sebacate)/poly(3-hydroxybutyrate)-TiO2 nanocomposites: fabrication and characterisation - Roether, Judith; Rai, Ranjana; Wolf, R.; Tallawi, Marwa; Boccaccini, Aldo R. (Materials Science and Technology, 2014)
Novel Nanocomposite films containing TiO2 nanoparticles incorporated in blend matrices of biocompatible and bioresorbable polymers, namely poly(glycerol sebacate) (PGS) and poly(3-hydroxybutyrate) P(3HB), were developed. The samples were fabricated via a sequential step of solvent casting followed by cross-linking. PGS/P(3HB) blends (controls) were fabricated in two different ratios, i.e. 7 : 1 and 8 : 1. Varying amounts of TiO2 nanoparticles (1 and 2 vol.-%) were incorporated into the matrices. SEM studies revealed that the TiO2 particles were distributed both within the matrix and on the surface of the films thus imparting surface nanotopography and increasing the surface roughness. These microstructural features combined with the cumulative effect of blending of the two polymeric systems influenced the wettability, chemical and mechanical properties of the films. In vitro degradation of the fabricated matrices in PBS medium over a 30 day period confirmed that the composites undergo weight loss and mechanical, chemical and surface topography changes. The nanocomposites constitute model biodegradable organic-inorganic systems suitable for tissue engineering applications.
Keywords: Nanocomposite; TiO2; Nanoparticles; Poly(glycerol sebacate); Poly(3-hydroxybutyrate)

Biomimetic poly(glycerol sebacate) (PGS) membranes for cardiac patch application - Rai, Ranjana; Tallawi, Marwa; Barbani, Niccoletta; Frati, Caterina; Madeddu, Denise; Cavali, Stefano; Graiani, Gallia; Quaini, Frederico; Schubert, Dirk W.; Roether, Judith; Rosellini, Elisabetta; Boccaccini, Aldo R. (Materials Science and Engineering C, 2013)
In this study biomimetic poly(glycerol sebacate) PGS matrix was developed for cardiac patch application. The rationale was that such matrices would provide conducive environment for the seeded cells at the interphase with PGS. From the microstructural standpoint, PGS was fabricated into dense films and porous PGS scaffolds. From the biological aspect, biomimetic PGS membranes were developed via covalently binding peptides Tyr-Ile-Gly-Ser-Arg (YIGSR) and Gly-Arg-Gly-Asp-Ser-Pro (GRGDSP), corresponding to the epitope sequences of laminin and fibronectin, respectively onto the surface. To improve and enhance homogenous binding of peptides onto the PGS surface, chemical modification of its surface was carried out. A sequential regime of alkaline hydrolysis with 0.01 M NaOH for 5 min and acidification with 0.01 M HCl for 25 s was optimal. More COOH chemical group was exposed without causing deleterious effect on the bulk properties of the polymer as revealed by the physicochemical analysis carried out. HPLC analysis, chemical imaging and ToF-SIMS were able to establish the successful homogenous functionalization of PGS membranes with the peptides. Finally, the developed biomimetic membranes supported the adhesion and growth of rat and human cardiac progenitor cells.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biomim
Keywords: Poly(glycerol sebacate); Cardiac patch; Biomimetic; Surface modification; Laminin; Fibronectin

Development and characterization of novel electrically conductive PANI-PGS composites for cardiac tissue engineering applications - Qazi, Taimoor H.; Rai, Ranjana; Dippold, Dirk; Roether, Judith; Schubert, Dirk W.; Rosellini, Elisabetta; Barbani, Niccoletta; Boccaccini, Aldo R. (Acta Biomaterialia, 2014)
Cardiovascular diseases, especially myocardial infarction, are the leading cause of morbidity and mortality in the world, also resulting in huge economic burdens on national economies. A cardiac patch strategy aims at regenerating an infarcted heart by providing healthy functional cells to the injured region via a carrier substrate, and providing mechanical support, thereby preventing deleterious ventricular remodeling. In the present work, polyaniline (PANI) was doped with camphorsulfonic acid and blended with poly(glycerol-sebacate) at ratios of 10, 20 and 30 vol.% PANI content to produce electrically conductive composite cardiac patches via the solvent casting method. The composites were characterized in terms of their electrical, mechanical and physicochemical properties. The in vitro biodegradability of the composites was also evaluated. Electrical conductivity increased from 0 S cm for pure PGS to 0.018 S cm for 30 vol.% PANI-PGS samples. Moreover, the conductivities were preserved for at least 100 h post fabrication. Tensile tests revealed an improvement in the elastic modulus, tensile strength and elasticity with increasing PANI content. The degradation products caused a local drop in pH, which was higher in all composite samples compared with pure PGS, hinting at a buffering effect due to the presence of PANI. Finally, the cytocompatibility of the composites was confirmed when C2C12 cells attached and proliferated on samples with varying PANI content. Furthermore, leaching of acid dopants from the developed composites did not have any deleterious effect on the viability of C2C12 cells. Taken together, these results confirm the potential of PANI-PGS composites for use as substrates to modulate cellular behavior via electrical stimulation, and as biocompatible scaffolds for cardiac tissue engineering applications. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Biocompatibility; Cardiac patch; Conductive composite; Poly(glycerol-sebacate); Polyaniline

Effect of Substrate Mechanics on Cardiomyocyte Maturation and Growth - Tallawi, Marwa; Rai, Ranjana; Boccaccini, Aldo R.; Aifantis, Katerina E. (Tissue Engineering - Part B: Reviews, 2015)
Cardiac tissue engineering constructs are a promising therapeutic treatment for myocardial infarction, which is one of the leading causes of death. In order to further advance the development and regeneration of engineered cardiac tissues using biomaterial platforms, it is important to have a complete overview of the effects that substrates have on cardiomyocyte (CM) morphology and function. This article summarizes recent studies that investigate the effect of mechanical cues on the CM differentiation, maturation, and growth. In these studies, CMs derived from embryos, neonates, and mesenchymal stem cells were seeded on different substrates of various elastic modulus. Measuring the contractile function by force production, work output, and calcium handling, it was seen that cell behavior on substrates was optimized when the substrate stiffness mimicked that of the native tissue. The contractile function reflected changes in the sarcomeric protein confirmation and organization that promoted the contractile ability. The analysis of the literature also revealed that, in addition to matrix stiffness, mechanical stimulation, such as stretching the substrate during cell seeding, also played an important role during cell maturation and tissue development.

Medium chain length polyhydroxyalkanoates, promising new biomedical materials for the future - Rai, Ranjana; Keshavarz, T.; Roether, J. A.; Boccaccini, Aldo R.; Roy, I. (Materials Science & Engineering R-Reports, 2011)
Medium chain length polyhydroxyalkanoates, mcl-PHAs (C6-C 14 carbon atoms), are polyesters of hydroxyalkanoates produced mainly by fluorescent Pseudomonads under unbalanced growth conditions. These mcl-PHAs which can be produced using renewable resources are biocompatible, biodegradable and thermoprocessable. They have low crystallinity, low glass transition temperature, low tensile strength and high elongation to break, making them elastomeric polymers. Mcl-PHAs and their copolymers are suitable for a range of biomedical applications where flexible biomaterials are required, such as heart valves and other cardiovascular applications as well as matrices for controlled drug delivery. Mcl-PHAs are more structurally diverse than short chain length PHAs and hence can be more readily tailored for specific applications. Composites have also been fabricated using mcl-PHAs and their copolymers, such as poly (3-hydroxyoctanoate) [P(3HO)] combined with single walled carbon nanotubes and poly(3-hydroxbutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] combined with hydroxyapatite. Because of these attractive properties of biodegradability, biocompatibility and tailorability, Mcl-PHAs and their composites are being increasingly used for biomedical applications. However, studies remain limited mainly to P(3HO) and the copolymer P(3HB-co-3HHx), which are the only mcl-PHAs available in large quantities. In this review we have consolidated current knowledge on the properties and biomedical applications of these elastomeric mcl-PHAs, their copolymers and their composites. © 2010 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.medium
Keywords: Biomedical applications; Composites; Poly(3-hydroxyoctanoate); Polyesters; Polyhydroxyalkanoates; Tissue engineering

Myocardial tissue engineering - Chen, Q. Z.; Harding, S. E.; Rai, Ranjana; Boccaccini, Aldo R. (Elsevier Inc., 2014)
In the pursuit of engineering a functional myocardium, studies integrating highly innovative research in stem cells and biomaterials development have opened new frontiers. Stringent properties like biocompatibility, ability to foster cells, biodegradability and mechanical compliance have been the norm for material selection. Fabrication techniques implemented individually or in conjunction have been used to fabricate scaffolds that best mimic the anisotropic nature of the cardiac extracellular matrix (ECM). Such biomimetic scaffolds provide topographical cues for contact guidance to align cells required to achieve synchronous electrophysiological coupling of the engineered myocardium to the native heart. Various functionalization strategies in tandem with scaffold fabrication designs and bioreactor studies have been undertaken to achieve vascularization in the engineered cardiac construct.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Biocompatibility; Biomaterials; Myocardial tissue engineering (MTE); Stem cells; Vascularization

Novel PGS/PCL electrospun fiber mats with patterned topographical features for cardiac patch applications - Tallawi, Marwa; Dippold, Dirk; Rai, Ranjana; D'Atri, D.; Roether, Judith; Schubert, Dirk W.; Rosellini, E.; Engel, Felix; Boccaccini, Aldo R. (Materials Science and Engineering C, 2016)
Nano- and micro-scale topographical features play a critical role in the induction and maintenance of various cellular properties and functions, including morphology, adhesion, gene regulation, and cell-to-cell communication. In addition, recent studies have indicated that the structure and function of heart tissue are also sensitive to mechanical cues at the nano- and micro-scale. Although fabrication methods exist for generating topographical features on polymeric scaffolds for cell culture, current techniques, especially those with nano-scale resolution, are typically complex, prohibitively expensive and not accessible to most biology laboratories. Here, we present a simple and tunable fabrication method for the production of patterned electrospun fibers that simulate the complex anisotropic and multi-scale architecture of cardiac tissue, to promote cardiac cell alignment. This method is based on the combination of electrospinning and soft lithography techniques, in which electrospun fibers, based on a blend of poly(glycerol sebacate) and poly(caprolactone), were collected on a patterned Teflon-coated silicon wafer with imprinted topographical features. Different surface topographies were investigated, such as squares and grooves, with constant or different interspatial distances. In vitro cell culture studies successfully demonstrated the alignment of both C2C12 myoblasts and neonatal rat cardiomyocytes on fabricated electrospun patterned surfaces. C2C12 cells were cultured over a period of 72h to study the effect of topographical cues on cell morphology. Cells attached within the first 8h after seeding and after 24h most of the cells started to align responding to the topographical cues. Similarly, cardiomyocytes responded to the topographical features by aligning themselves and by expressing Connexin 43 along cellular junctions. Summarizing, we have developed a new method with the potential to significantly promote cardiac tissue engineering by fabricating electrospun fibers with defined topographical features to guide and instruct donor and/or host cells.
EVALuna:34665

Poly-3-hydroxyoctanoate P(3HO), a Medium Chain Length Polyhydroxyalkanoate Homopolymer from Pseudomonas mendocina - Rai, Ranjana; Yunos, Darmawati M.; Boccaccini, Aldo R.; Knowles, Jonathan C.; Barker, Ian A.; Howdle, Steven M.; Tredwell, Gregory D.; Keshavarz, Tajalli; Roy, Ipsita (Biomacromolecules, 2011)
Pseudomonas mendocina was found to produce a unique homopolymer of poly(3-hydroxyoctanoate), P(3HO), rather than a copolymer, when grown on sodium octanoate as the sole carbon source. Although this polymer has been produced by other organisms, interestingly this is the first time an absolute homopolymer has been produced by a wild type organism. In addition, a detailed study on the effects of different extraction methods on the yield, molecular weight, thermal properties, and lipopolysaccharide content of P(3HO) has been carried out. The organism was able to accumulate P(3HO) up to 31.38% of its dry cell weight within 48 h in mineral salt medium. Characterization of the monomer was carried out using FTIR, GC-MS, 13C, 1H, and HSQC NMR spectroscopy. The polymer had a crystallinity of 37.5%, Young's modulus value of 11.6 MPa and contact angle of 77.3°. Microstructural studies of solvent cast polymer films revealed a smooth surface topography with a root-mean-square roughness value of 0.238 μm. © 2011 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.poly3h

Poly(Glycerol Sebacate) Films Modified by Thermal Proteins for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Costa, Marina; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Biomedical Engineering, 2013)
Scaffolds for cardiac tissue engineering must be designed to achieve adequate degradation kinetics and mechanical properties. In this study, bulk modification of poly(glycerol sebacate) (PGS) with different concentrations of thermal proteins (TP) was investigated to tailor the degradation properties of PGS. TP are poly-amino acids formed by heating a mixture of amino acids with minimal proportions of glutamic or aspartic acid. The degradation study of TP-PGS was performed in vitro in phosphate buffered saline (PBS) solution over a 21 day period. Results showed that the degradation rate of PGS increased with increasing content of TP. After 21 days in PBS, degradation weight loss values of 9.40% ± 0.07, 7.3% ± 0.8 and 6.0% ± 0.4 were determined for PGS-TP-2g, PGS-TP-0.01g and PGS-control, respectively. The studies also showed that TP altered the mechanical properties and surface hydrophilicity of PGS.
Keywords: Thermal proteins; degradation; poly(glycerol sebacate); cardiac tissue engineering

Poly(Glycerol Sebacate)/Poly(Butylene Succinate-Butylene Dilinoleate) Fibrous Scaffolds for Cardiac Tissue Engineering - Tallawi, Marwa; Zebrowski, David; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; El Fray, Miroslawa; Engel, Felix; Aifantis, Katerina E.; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2015)
The present article investigates the use of a novel electrospun fibrous blend of poly(glycerol sebacate) (PGS) and poly(butylene succinate-butylene dilinoleate) (PBS-DLA) as a candidate for cardiac tissue engineering. Random electrospun fibers with various PGS/PBS-DLA compositions (70/30, 60/40, 50/50, and 0/100) were fabricated. To examine the suitability of these fiber blends for heart patches, their morphology, as well as their physical, chemical, and mechanical properties were measured before examining their biocompatibility through cell adhesion. The fabricated fibers were bead-free and exhibited a relatively narrow diameter distribution. The addition of PBS-DLA to PGS resulted in an increase of the average fiber diameter, whereas increasing the amount of PBS-DLA decreased the hydrophilicity and the water uptake of the nanofibrous scaffolds to values that approached those of neat PBS-DLA nanofibers. Moreover, the addition of PBS-DLA significantly increased the elastic modulus. Initial toxicity studies with C2C12 myoblast cells up to 72 h confirmed nontoxic behavior of the blends. Immunofluorescence analyses and scanning electron microscopy analyses confirmed that C2C12 cells showed better cell attachment and proliferation on electrospun mats with higher PBS-DLA content. However, immunofluorescence analyses of the 3-day-old rat cardiomyocytes cultured for 2 and 5 days demonstrated better attachment on the 70/30 fibers containing well-aligned sarcomeres and expressing high amounts of connexin 43 in cellular junctions indicating efficient cell-to-cell communication. It can be concluded, therefore, that fibrous PGS/PBS-DLA scaffolds exhibit promising characteristics as a biomaterial for cardiac patch applications.

Poly(glycerol sebacate)(butylene succinate-dilinoleate) blends as candidate materials for cardiac tissue engineering - Boccaccini, Aldo R.; Aifantis, K.; Tallawi, Marwa; Rai, Ranjana; R-Gleixner, M.; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate‐dilinoleate) (PBS‐DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS‐DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS‐DLA blends were measured and compared. By adding PBS‐DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS‐DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS‐DLA films. Furthermore, addition of PBS‐DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS‐DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS‐DLA addition led to decreased degradation rate of the films. Furthermore the PBS‐DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS‐DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: myoblasts; poly (butylene succinate-dilinoleate); cardiac tissue engineering; mechanobiology; substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, Miroslawa; Aifantis, K.; Boccaccini, Aldo R.; et al. (WILEY-V C H VERLAG GMBH, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approaches.
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Poly(glycerol sebacate){Poly(butylene succinate-dilinoleate) Blends as Candidate Materials for Cardiac Tissue Engineering - Tallawi, Marwa; Rai, Ranjana; Ramsperger-Gleixner, Martina; Roerick, Olaf; Weyand, Michael; Roether, Judith; Schubert, Dirk W.; Kozlowska, A.; El Fray, M.; Aifantis, K.; Boccaccini, Aldo R.; et al. (Macromolecular Symposia, 2013)
Poly (glycerol sebacate) (PGS) and poly (butylene succinate-dilinoleate) (PBS-DLA) are biodegradable polymers with potential application in cardiac tissue engineering. In the present study novel blends comprising PGS prepolymer and PBS-DLA were prepared with varying compositions (70/30, 60/40, 50/50, 40/60, 30/70 and 0/100 in weight percentage). The physical, chemical, and mechanical properties of the PGS/PBS-DLA blends were measured and compared. By adding PBS-DLA to PGS the need for curing PGS prepolymer was eliminated, as the blended films are chemically stable. With increasing amount of PBS-DLA the hydrophobicity of the blend system increased reaching values close to that of neat PBS-DLA films. Furthermore, addition of PBS-DLA significantly affected the mechanical properties of the blends, i.e. the elastic modulus of the blends was enhanced with increasing PBS-DLA addition from 1.2 MPa to 54 MPa. At the same time, PBS-DLA addition led to decreased degradation rate of the films. Furthermore the PBS-DLA counteracted the acidity of the free carboxylic groups on the free end chains of the PGS prepolymer. In vitro cytocompatibility studies indicated high biocompatibility. Taken together the results confirm that the novel PGS/PBS-DLA matrices exhibit promising characteristics as a biomaterial for application in cardiac regeneration approache
Keywords: cardiac tissue engineering; mechanobiology; myoblasts; poly (butylene succinate-dilinoleate); substrate stiffness

Polymers for myocardial tissue engineering - Roether, Judith; Jawad, H.; Rai, Ranjana; Ali, N. N.; Harding, S. E.; Boccaccini, Aldo R. (CRC Press, 2013)
Cardiovascular disease (CVD) is the leading cause of death in the industrialized world (Lloyd-Jones et al. 2010). Heart attacks are the main cause of death in patients with CVD, although damage to heart muscle can also occur from infection, drugs, alcohol, chemotherapeutic agents, or because of congenital conditions. According to available statistical information (www.bhf.org.uk), approximately 30% of patients suffering from heart attacks each year die suddenly before reaching hospital. In the remaining patients who survive the initial acute event, the damage sustained to the heart may eventually develop heart failure. A heart attack, known as myocardial infarction (MI), occurs when one or more of the blood vessels supplying the heart suddenly occlude. These vessels are the coronary arteries, and when blocked abruptly, there is a sudden decrease in the supply of nutrients and oxygen to the portion of heart muscle supplied by the artery. If blood flow is not restored rapidly, the result is irreversible cell death within the affected part of the heart muscle.
CRIS-Team Scopus Importer:2022-08-05

Preparation and characterization of PHBV microsphere/45S5 bioactive glass composite scaffolds with vancomycin releasing function - Li, Wei; Ding, Yaping; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2014)
PHBV microsphere/45S5 bioactive glass (BG) composite scaffolds with drug release function were developed for bone tissue engineering. BG-based glass-ceramic scaffolds with high porosity (94%) and interconnected pore structure prepared by foam replication method were coated with PHBV microspheres (nominal diameter = 3.5 μm) produced by water-in-oil-in-water double emulsion solvent evaporation method. A homogeneous microsphere coating throughout the porous structure of scaffolds was obtained by a simple dip coating method, using the slurry of PHBV microspheres in hexane. Compressive strength tests showed that the microsphere coating slightly improved the mechanical properties of the scaffolds. It was confirmed that the microsphere coating did not inhibit the bioactivity of the scaffolds in SBF. Hydroxyapatite crystals homogeneously grew not only on the struts of the scaffolds but also on the surface of microspheres within 7 days of immersion in SBF. Vancomycin was successfully encapsulated into the PHBV microspheres. The encapsulated vancomycin was released with a dual release profile involving a relatively low initial burst release (21%) and a sustained release (1 month), which is favorable compared to the high initial burst release (77%) and short release period (4 days) measured on uncoated scaffolds. The developed bioactive composite scaffold with drug delivery function has thus the potential to be used advantageously in bone tissue engineering. © 2014 Elsevier B.V. All rights reserved.
Keywords: Bioglass; drug delivery; PHBV; scaffold; tissue engineering; vancomycin

Preparation and characterization of PHBV microsphere/45S5 bioactive glass composite scaffolds with vancomycin releasing function - Li, Wei; Ding, Yaping; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Science and Engineering C, 2014)
PHBV microsphere/45S5 bioactive glass (BG) composite scaffolds with drug release function were developed for bone tissue engineering. BG-based glass-ceramic scaffolds with high porosity (94%) and interconnected pore structure prepared by foam replication method were coated with PHBV microspheres (nominal diameter = 3.5 μm) produced by water-in-oil-in-water double emulsion solvent evaporation method. A homogeneous microsphere coating throughout the porous structure of scaffolds was obtained by a simple dip coating method, using the slurry of PHBV microspheres in hexane. Compressive strength tests showed that the microsphere coating slightly improved the mechanical properties of the scaffolds. It was confirmed that the microsphere coating did not inhibit the bioactivity of the scaffolds in SBF. Hydroxyapatite crystals homogeneously grew not only on the struts of the scaffolds but also on the surface of microspheres within 7 days of immersion in SBF. Vancomycin was successfully encapsulated into the PHBV microspheres. The encapsulated vancomycin was released with a dual release profile involving a relatively low initial burst release (21%) and a sustained release (1 month), which is favorable compared to the high initial burst release (77%) and short release period (4 days) measured on uncoated scaffolds. The developed bioactive composite scaffold with drug delivery function has thus the potential to be used advantageously in bone tissue engineerin
Keywords: tissue engineering; vancomycin; PHBV; scaffold; drug delivery; Bioglass

Sterilization effects on the physical properties and cytotoxicity of poly (glycerol sebacate) - Rai, Ranjana; Tallawi, Marwa; Roether, Judith; Detsch, Rainer; Barbani, Niccoletta; Rosellini, Elisabeth; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Letters, 2013)
The influence of conventional sterilization methods such as gamma irradiation, ethylene oxide treatment and steam exposure on the physical properties of poly(glycerol sebacate) (PGS) was investigated. Scanning electron microscope (SEM) observations, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and Raman spectra demonstrated that the applied sterilization methods do not induce adverse surface modifications. The sterilized samples also maintained their thermal and mechanical properties post-sterilization. In addition, gamma sterilized PGS films did not induce any toxicity when films were in contact with murine fibroblast 313 cells. PGS is compatible for all the sterilization methods used in this study, which is of relevance for the wider application of PGS in medical devices. (C) 2013 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.steril
Keywords: Biocompatibility; Biopolymers; Gamma irradiation; Poly(glycerol sebacate); Sterilization

Strategies for the chemical and biological functionalization of scaffolds for cardiac tissue engineering: A review - Tallawi, Marwa; Rosellini, Elisabetta; Barbani, Niccoletta; Cascone, Maria Grazia; Rai, Ranjana; Saint-Pierre, Guillaume; Boccaccini, Aldo R. (Journal of the Royal Society Interface, 2015)
The development of biomaterials for cardiac tissue engineering (CTE) is challenging, primarily owing to the requirement of achieving a surface with favourable characteristics that enhances cell attachment and maturation. The biomaterial surface plays a crucial role as it forms the interface between the scaffold (or cardiac patch) and the cells. In the field of CTE, synthetic polymers (polyglycerol sebacate, polyethylene glycol, polyglycolic acid, poly-L-lactide, polyvinyl alcohol, polycaprolactone, polyurethanes and poly(N-isopropylacrylamide)) have been proven to exhibit suitable biodegradable and mechanical properties. Despite the fact that they show the required biocompatible behaviour, most synthetic polymers exhibit poor cell attachment capability. These synthetic polymers are mostly hydrophobic and lack cell recognition sites, limiting their application. Therefore, biofunctionalization of these biomaterials to enhance cell attachment and cell material interaction is being widely investigated. There are numerous approaches for functionalizing a material, which can be classified as mechanical, physical, chemical and biological. In this review, recent studies reported in the literature to functionalize scaffolds in the context of CTE, are discussed. Surface, morphological, chemical and biological modifications are introduced and the results of novel promising strategies and techniques are discussed.
Keywords: Biofunctionalization; Biological modification; Biomimetic scaffolds; Cardiac tissue engineering; Chemical modification

Synthesis, properties and biomedical applications of poly(glycerol sebacate) (PGS): A review - Rai, Ranjana; Tallawi, Marwa; Grigore, Alexandra; Boccaccini, Aldo R. (Progress in Polymer Science, 2012)
Poly(glycerol sebacate) (PGS) is a biodegradable polymer increasingly used in a variety of biomedical applications. This polyester is prepared by polycondensation of glycerol and sebacic acid. PGS exhibits biocompatibility and biodegradability, both highly relevant properties in biomedical applications. PGS also involves cost effective production with the possibility of up scaling to industrial production. In addition, the mechanical properties and degradation kinetics of PGS can be tailored to match the requirements of intended applications by controlling curing time, curing temperature, reactants concentration and the degree of acrylation in acrylated PGS. Because of the flexible and elastomeric nature of PGS, its biomedical applications have mainly targeted soft tissue replacement and the engineering of soft tissues, such as cardiac muscle, blood, nerve, cartilage and retina. However, applications of PGS are being expanded to include drug delivery, tissue adhesive and hard tissue (i.e., bone) regeneration. The design and fabrication of PGS based devices for applications that mimic native physiological conditions are also being pursued. Novel designs range from accordion-like honeycomb structures for cardiac patches, gecko-like surfaces for tissue adhesives to PGS (nano) fibers for extra cellular matrix (ECM) like constructs; new design avenues are being investigated to meet the ever growing demand for replacement tissues and organs. In less than a decade PGS has become a material of great scrutiny and interest by the biomedical research community. In this review we consolidate the valuable existing knowledge in the fields of synthesis, properties and biomedical applications of PGS and PGS-related biomaterials and devices. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.synthe
Keywords: Biocompatible; Bioresorbable polymers; PGS processing; Poly(glycerol sebacate); Tissue engineering

The homopolymer poly(3-hydroxyoctanoate) as a matrix material for soft tissue engineering - Rai, Ranjana; Boccaccini, Aldo R.; Knowles, Jonathan C.; Mordon, Nicola; Salih, Vehid; Locke, Ian C.; Moshrefi-Torbati, M.; Keshavarz, Tajalli; Roy, Ipsita (Journal of Applied Polymer Science, 2011)
The homopolymer poly(3-hydroxyoctanoate), produced from Pseudomonas mendocina with octanoate as a carbon feed, was studied as a potential biomaterial for soft tissue engineering, that is, as a cardiac patch and as matrices for skin tissue engineering. The polymer was fabricated into neat solvent-cast films of 5 and 10 wt %. Microstructural studies revealed the films as having a smooth surface topography with a root mean square value of 0.238 μm. The films also possessed moderate hydrophilicity when compared to other monomers of the polyhydroxyalkanoate family. Stress-strain curves of the films obtained was typical of that of elastomeric polymers. This elastomeric and flexible nature of the films makes them promising candidates for the proposed applications. Biocompatibility studies with the human adult low calcium temperature keratinocytes (HaCaT) keratinocyte cell line showed that the films were able to support the attachment, differentiation, and maturation of the HaCaT cells. In vitro degradation studies over a period of 4 months showed that the water absorption and weight loss increased progressively with time for the films. The films underwent hydrolytic degradation initiated on the surface and also showed an aging effect. © 2011 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.thehom
Keywords: biodegradable; biopolymer; elastomer; polyester

Tissue engineering of electrically responsive tissues using polyaniline based polymers: A review - Qazi, Taimoor Hasan; Rai, Ranjana; Boccaccini, Aldo R. (Biomaterials, 2014)
Conducting polymers have found numerous applications as biomaterial components serving to effectively deliver electrical signals from an external source to the seeded cells. Several cell types including cardiomyocytes, neurons, and osteoblasts respond to electrical signals by improving their functional outcomes. Although a wide variety of conducting polymers are available, polyaniline (PANI) has emerged as a popular choice due to its attractive properties such as ease of synthesis, tunable conductivity, environmental stability, and biocompatibility. PANI in its pure form has exhibited biocompatibility both invitro and invivo, and has been combined with a host of biodegradable polymers to form composites having a range of mechanical, electrical, and surface properties. Moreover, recent studies in literature report on the functionalization of polyaniline oligomers with end segments that make it biodegradable and improve its biocompatibility, two properties which make these materials highly desirable for applications in tissue engineering. This review will discuss the features and properties of PANI based composites that make them effective biomaterials, and it provides a comprehensive summary of studies where the use of PANI as a biomaterial component has enhanced cellular function and behavior. We also discuss recent studies utilizing functionalized PANI oligomers, and conclude that electroactive PANI and its derivatives show great promise in eliciting favorable responses from various cell lines that respond to electrical stimuli, and are therefore effective biomaterials for the engineering of electrically responsive biological tissues and organs. © 2014 Elsevier Ltd.
Keywords: Conducting polymers; Electrical stimulation; Polyaniline; Polyaniline oligomers; Tissue engineering